2015
DOI: 10.1249/mss.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure in Institutionalized Older Adults

Abstract: The high percent error scores indicate that the SWMini is of limited value for quantifying EE in the old and old-old. The accuracy could be improved by developing accurate age- and activity-specific algorithms. On the other hand, the SWMini can be used as a suitable device for researchers interested in specific levels and patterns of PA and sedentary behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Four studies could not be synthesised by meta-analysis as mean difference between activity monitors and criterion measurements were not provided12 31–33; thus, 60 studies were included in the meta-analysis (figure 1). 10 13 34–88 A total of 1946 participants were included, with a mean age of 35 years (range 20–86 years). The mean body mass index (BMI) was 24.9 kg/m 2 (range 21.8–31.6 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies could not be synthesised by meta-analysis as mean difference between activity monitors and criterion measurements were not provided12 31–33; thus, 60 studies were included in the meta-analysis (figure 1). 10 13 34–88 A total of 1946 participants were included, with a mean age of 35 years (range 20–86 years). The mean body mass index (BMI) was 24.9 kg/m 2 (range 21.8–31.6 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the absolute error rate was 28% compared with DLW measures, whereas we found a lower absolute error rate at about 20%. Martien, Seghers, Boen, and Delecluse (2015) also found SWMA underestimated EE in older adults during resting and three activity tasks using a portable gas analyzer as the criterion measure, with an overall absolute percent error of 14.1%. The current study is the first one to report the validity of SWMA in estimating EE in adolescents.…”
Section: Discussionmentioning
confidence: 78%
“…In some recent studies, TEE was evaluated by accelerometers in elderly residents (18,19). However, the validity of using an accelerometer for estimating TEE has not yet been described, and it is unclear whether TEE can be accurately measured by that method in inactive populations.…”
Section: Discussionmentioning
confidence: 99%
“…Percentage of fat mass (FM) was calculated as (body weight2FFM) divided by body weight. The CO2 production rate (rCO2) was calculated according to the following equation: rCO25 0.45543TBW3(1.0073 18 O elimination rate2 1.0413 2 H elimination rate) TEEDLW was calculated according to the following equation:…”
Section: Subjectsmentioning
confidence: 99%